VIDARBHA KONKAN GRAMIN BANK AND GONDIA’S ECONOMIC TRANSFORMATION: AN ANALYTICAL PERSPECTIVE - Fule, Ku Kavita Bihari; Gedam, Tatyaji K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper aims at analysing the Going concern prospects of Vidarbha Konkan Gramin Bank to the economic development of Gondia district during the period from 2012-13 to 2021-22. Through the emancipation of financial enabler, VKGB has significantly responded to financial especially in the advancement of rural banking, promotion of business and agricultural activities.. The study is a mixed research design approach that uses both quantitative data analysis methods and qualitative information data to assess the impact of VKGB in the targeted communities in terms of income, credit, employment opportunities as well as overall regional economic growth. The analysis provides evidence that VKGB has significantly improved credit access for the countryside thus increasing agricultural yield and the development of SMEs. In addition, through self-help group financing and micro financing, the bank has helped the most needy groups starting with women. While the Authority has recorded great strides, factors that are likely to hinder efficiency include; limited number of computers, high operating costs, lack of equal distribution of credit by the mobile telecommunication companies amongst other things. Thus, the study reiterates the agenda to advance VKGB policy improvements to advance its interventions as a potent tool that can underpin Gondia’s economic change. Based on these recommendations, it is suggested that authorities advocate for more adoption of efficient digital banking tools, increase efforts on the enhancement of the relevant financial literacy programs and promote the development of partnerships between government and institutions with the aim to achieve the higher level of development. The purpose of this paper is to highlight and describe the contribution of rural banking to economic development in regions of operation with the information intended to be of practical help to banking and development stakeholders.